Targeting brain regions of interest in functional near‐infrared spectroscopy—Scalp‐cortex correlation using subject‐specific light propagation models - Cai, Lin; Nitta, Tomonori; Yokota, Sho; Obata, Takayuki; Okada, Eiji; Kawaguchi, Hiroshi (Human brain mapping, 2021)
Targeting specific brain regions of interest by the accurate positioning of optodes (emission and detection probes) on the scalp remains a challenge for functional near‐infrared spectroscopy (fNIRS). Since fNIRS data does not provide any anatomical information on the brain cortex, establishing the scalp‐cortex correlation (SCC) between emission‐detection probe pairs on the scalp and the underlying brain regions in fNIRS measurements is extremely important. A conventional SCC is obtained by a geometrical point‐to‐point manner and ignores the effect of light scattering in the head tissue that occurs in actual fNIRS measurements. Here, we developed a sensitivity‐based matching (SBM) method that incorporated the broad spatial sensitivity of the probe pair due to light scattering into the SCC for fNIRS. The SCC was analyzed between head surface fiducial points determined by the international 10–10 system and automated anatomical labeling brain regions for 45 subject‐specific head models. The performance of the SBM method was compared with that of three conventional geometrical matching (GM) methods. We reveal that the light scattering and individual anatomical differences in the head affect the SCC, which indicates that the SBM method is compulsory to obtain the precise SCC. The SBM method enables us to evaluate the activity of cortical regions that are overlooked in the SCC obtained by conventional GM methods. Together, the SBM method could be a promising approach to guide fNIRS users in designing their probe arrangements and in explaining their measurement data. (1) For targeting brain regions of interest in functional near‐infrared spectroscopy, scalp‐cortex correlation based on light propagation provides a precise mapping between scalp locations and brain regions. (2) The comparisons between sensitivity‐based matching and geometrical matching methods demonstrate that consideration of light scattering and individual anatomical variations are critical factors affecting scalp‐cortex correlation. (3) The group‐wise scalp‐cortex correlation index obtained by the sensitivity‐based matching could be a promising alternative to accurately targeting brain regions of interest.